The Impact of Social Policy on Economic Inequality in the Era of Digital Transformation: A Sociological Analysis and Public Management - Yorman (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
The era of digital transformation has brought significant changes to the global social and economic structure. In Indonesia, the development of information technology plays a dual role on the one hand to increase economic efficiency and opportunities, but on the other hand widens the social gap between the groups of people who have digital access and those who are left behind. This article aims to analyze the impact of social policies on economic inequality in the context of digital transformation, using an interdisciplinary approach between sociology and public management. This study uses a descriptive qualitative method through literature studies, policy analysis, and secondary data from reports from the Central Statistics Agency and the Ministry of Communication and Informatics. The results of the study show that social policies that are adaptive to digital developments are able to reduce economic inequality through increasing digital literacy, equitable distribution of technological infrastructure, and digital-based community economic empowerment. However, imbalances in policy implementation, especially in disadvantaged areas, lead to a digital divide that strengthens social stratification. This study emphasizes the need for integration between social strategies and inclusive public management, so that digital policies can function as an instrument for equitable distribution of welfare.